(untitled) (American Journal of Islam and Society, 2017)
When I was asked to review this piece for AJISS, I was excited to see scholarly work relating the Palestinian-Israeli conflict to neoliberalism. Reading the paper only heightened my enthusiasm; by invoking neoliberalism the author adds new insights into the nature of this conflict and why it persists. More often than not, we try to understand this conflict in terms of nationalism or religion. Thus framing it as a clash of intractable ideologies, which allows us to blame it on some uncompromising Islamic extremists and Zionist settlers, has become convenient – although neither is representative of the majority of either the Palestinians or the Israelis. Given this approach, we in the West have a tendency to look upon Israelis and/or Palestinians as the cause of their own problem. We scratch our heads when they do not come to an agreement, throw up our hands when the next president’s peace plan fails, and figure that those people are just that way – always have been and always will be. Not only is this viewpoint intellectually weak, but it is politically damaging because it ignores the true causes of the conflict and justifies indifference to violations of human rights.